Friction stir welding using rice husk on aluminium 6061 - Jajuli, Sarah Syafiqah (2021)
Conventional synthesized silver nanoparticles (AgNP) often correlated with harmful chemicals and by-products, consumed large amount of energy and involved complex procedure. Therefore, green synthesis of AgNP which offers eco-friendly and cost-effective method in synthesizing AgNP was proposed. This study used banana peel extract (BPE) and pineapple peel extract (PPE) as a reducing agent and stabilizer, and silver nitrate (AgNO3) as a metal salt precursor. Volume of peel extracts, concentration of AgNO3, reaction temperature and incubation time were optimized and the AgNP were characterized. The optimum conditions to produce BPE-AgNP and PPE-AgNP were successfully investigated. Total Phenolic Compound (TPC) analysis showed that BPE has higher phenols content than PPE which is 14.671 mgGAE/g and 8.479 mgGAE/g respectively. Visible spectrum displayed surface plasmon resonance (SPR) peak at 430 nm and 450 nm for BPE-AgNP and PPE-AgNP respectively. X-ray diffraction (XRD) displayed both BPE-AgNP and PPE-AgNP has face centered cubic crystalline nature. FESEM micrograph revealed both BPE-AgNP and PPE-AgNP are almost spherical with the particles size of 30.99 ± 9.47 nm and 21.6 ± 7.01 nm respectively. Energy dispersive X-ray spectroscopy (EDX) analysis showed the highest peak at 3 KeV which is in silver region, confirming the presence of elemental silver. Fourier transform infrared spectroscopy (FTIR) analysis confirmed the functional group responsible as reducing agent in the transformation of Ag+ to Ag0 and resulted to the stabilization of AgNP structure. BPE-AgNP and PPE-AgNP showed good potential as a catalyst for methylene blue (MB) and methyl orange (MO) decolorization. Decolorization kinetics observation indicated MB decolorization was best fitted to first order and intraparticle diffusion model for BPE-AgNP and pseudo first order model for PPE-AgNP. Meanwhile, MO decolorization was best fitted to pseudo-second order model for both BPE-AgNP and PPE-AgNP.